Feasibility of dose enhancement assessment: preliminary results by means of Gd-infused polymer gel dosimeter and Monte Carlo study - Santibáñez, M. (2018)
This work reports the experimental development of an integral Gd-infused dosimeter suitable for Gd dose enhancement assessment along with Monte Carlo simulations applied to determine the dose enhancement by radioactive and X-ray sources of interest in conventional and electronic brachytherapy. In this context, capability to elaborate a stable and reliable Gd-infused dosimeter was the first goal aimed at direct and accurate measurements of dose enhancement due to Gd presence. Dose-response was characterized for standard and Gd-infused PAGAT polymer gel dosimeters by means of optical transmission/absorbance. The developed Gd-infused PAGAT dosimeters demonstrated to be stable presenting similar dose-response as standard PAGAT within a linear trend up to 13 Gy along with good post-irradiation readout stability verified at 24 and 48 hours. Additionally, dose enhancement was evaluated for Gd-infused PAGAT dosimeters by means of Monte Carlo (PENELOPE) simulations considering scenarios for isotopic and X-ray generator sources. The obtained results demonstrated the feasibility of obtaining a maximum enhancement around of (14±1)% for 192Ir source and an average enhancement of (70±13)% for 241Am. However, dose enhancement up to (267±18)% may be achieved if suitable filtering is added to the 241Am source. On the other hand, optimized X-ray spectra may attain dose enhancements up to (253±22) %, which constitutes a promising future alternative for replacing radioactive sources by implementing electronic brachytherapy achieving high dose levels.